Letter : Basque Children's Committee - Prain, Robert
1942-01-21 038-0027-001 Tel. Whaley Bridge 227. (Light and Liberty) Electrical Trades Union. EXECUTIVE COUNCIL. All Communications to be addressed to: E.W. BUSSEY, General Secretary. IMPORTANT. PIease deal with one subject only. General Office: OLLERENSHAW HALL, WHALEY BRIDGE, STOCKPORT, CHESHIRE. PLEASE QUOTE IN REPLY. Your Ref. Our ref RP/LB. SUBJECT Basque Children's Committee. 21st Jan. 1942. Sir Walter Citrine, General Secretary, Trades Union Congress, Transport House, Smith Square, LONDON, S.W.1. Dear Sir, My Executive Council will be exceedingly obliged if the Trades Union Congress can give them any information as to the Basque Children's Committee. We have received a letter from our London District Committee containing the two following suggestions:- "A grant towards the expenses of the Home from the National Solidarity Fund." "A request that the General Council approach the Government to subsidise the Home for the future." The Committee further suggests that our Executive should take the matter up with the General Council of the Trades Union Congress and ask for their support. Yours faithfully, for the ELECTRICAL TRADES UNION. Robert Prain Asst. General Secretary. R.O. P.T.O 292/946/38/27(I)